If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(t + 7) = 7t + -3 Reorder the terms: 3(7 + t) = 7t + -3 (7 * 3 + t * 3) = 7t + -3 (21 + 3t) = 7t + -3 Reorder the terms: 21 + 3t = -3 + 7t Solving 21 + 3t = -3 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 21 + 3t + -7t = -3 + 7t + -7t Combine like terms: 3t + -7t = -4t 21 + -4t = -3 + 7t + -7t Combine like terms: 7t + -7t = 0 21 + -4t = -3 + 0 21 + -4t = -3 Add '-21' to each side of the equation. 21 + -21 + -4t = -3 + -21 Combine like terms: 21 + -21 = 0 0 + -4t = -3 + -21 -4t = -3 + -21 Combine like terms: -3 + -21 = -24 -4t = -24 Divide each side by '-4'. t = 6 Simplifying t = 6
| (x^2+7x+10)(x^2+7x+10)(x^2+7x+10)=0 | | -x=-y+2 | | 18=2(3k+1)-4 | | 4x+48=12x | | x^2+10=154 | | 2.5x+6=60 | | 2y^2+3y-35= | | 8y=33-5y | | 9d-9=18 | | 9u=4u+35 | | 6m+4m-m+5=23 | | 6(x+3)-20=32 | | 3x-5x+1=8-2x | | 2x+3+0.75= | | 9y^2+18y+8= | | x^2-16x-132=0 | | 10=30(20)+b | | y=ln(x+2)-4 | | 10(x-2)+12(x+4)=x | | 9x-37=12x+23 | | -7y-2x=-13 | | 5.5x+1.2-0.3=7.2x-3 | | 13=4x?9 | | 12+x^2=8y-y^2 | | -2[3+4(x-1)]=x | | x+2x+3x=306 | | -3-66x=9 | | 5.2x=3x | | 1=2(12) | | 196-36x^2=0 | | 6x=306 | | -16x+3=37+x |